Family Business in Vietnam : Family Owned Structures and the Current National Economic Situation - Suhonen, Camtu (2018)
This thesis involves a landscape of the current economic situation in Vietnam, and the role family-owned business plays in the nation’s trading history. The life of a family business has been regulated under the communist system and how the communist has upset the position of private-owned enterprises throughout the country. From 2010 to 2017, there are significant numbers of bankrupted family-owned businesses even though Vietnam has been one of the world’s fastest-growing economies; it has benefited from the influx of foreign investors. The negative impacts of these investments have made towards domestic enterprises that discussed intensely by a qualitative method. The focus of modern bankruptcy legislation and trade debt restructuring practices no longer stand on the rejection of failed organizations but on the upgrading of the financial and managerial structure of debtors experiencing a financial crisis to enable the recovery and preservation of the business. Bankruptcy in Vietnam refers to enterprises having foreign-invested enterprises, cooperatives, and cooperative unions hereafter collectively referred to as enterprises. Unlike certain societies, this makes no change to individuals. Bankruptcy in Vietnam lies under the law of the people’s courts were local enterprises are centered. A lot of delays occur in the enforcement, and there is the need to establish a transparent procedure. The private sector is the core backbone supporting the economy. The success of a family business inevitably comes down to the art if integrating and harmonizing the needs of family, ownership, and business. Unfortunately, most companies have failed and rendered bankrupt and closed.  While others are headed there because of many factors that to be dealt with but have not. All interviews were records for this thesis had constructed by face-to-face, phone calls as well as messengers because these are core sources in term of collected data. Thematic analysis is one of the best ways to extract data and to produce quality results. By any mean, the entrepreneurial spirit of Vietnamese professionals was also discussed and whether local entrepreneurship could be boosted in light of the recent economic reforms that are currently in place. The study had figured out the weakest management in businesses based families and had suggested how the up-coming self-entrepreneurs overcome their father’s footsteps.